David Kelley et la politique de la complicité - Jean-Pierre Esquenazi (Mise au Point)
Television is linked to its family broadcasting; American history reminds us of it. And television series are tied to this context. They multiply signs of recognition. David Kelley, Ally Mc Beal or Boston Legal's producer, likes to play with this necessity. He creates a relation of complicity between his figures and the viewer. This text studies his main methods.